Metode Forward Chaining dalam Sistem Pakar Diagnosis Penyakit pada Tanaman Kelapa Sawit - Aghy Gilar Pratama; Andrianto Heri Wibowo; Septia Nurhalimah (Prosiding SISFOTEK, 2019)
Diagnosis of diseases in plants is needed to determine pests or diseases that attack the plant through the symptoms found. This is done in order to find the best healing solutions for oil palm plants that have been stricken with disease, to minimize crop failure. Therefore we need a computerized expert system to replace the conventional system of diagnosing oil palm plant diseases in order to get a more precise and accurate healing solution without having to wait for the expert. Oil palm plantations are one of the types of plantation crops in Indonesia that occupy important positions and develop rapidly, both those that belong to individuals or companies. This is because of the many plants that produce oil or fat are oil palm with the largest economic value per hectare in the world. Not only that, oil from palm oil is also used for fuel (biodiesel). Palm oil pests and diseases are factors that can interfere with the growth and productivity of these plants. Attacking pests and plant diseases can be seen from the physical symptoms, leaves, stems, roots, and from the palm fruit produced. The lack of knowledge of plantation workers about pests and diseases of oil palm plants and the difficulty in consulting directly with an expert makes it difficult for plantation workers to deal with diseases of oil palm plantations resulting in a lack of crop yields from these plants. From these problems many plantation workers cut down trees in an effort to eradicate pests and diseases of oil palm plants. So there is need for research to build expert system software to diagnose oil palm plant diseases. The inference process to diagnose the symptoms of palm oil pests and diseases and the types of diseases using the forward chaining method.